Sistemas de manejo e variedades de cana-de-açúcar na composição da vinhaça de cachaça de alambique - Mattos, Danilo Sidney (Universidade Federal de São Carlos, 2017)
The productive chain of the alembic cachaca is one of the most promising in the developing agroindustry in Brazil. The vinasse is the main waste of the productive activity, due to the large volume generated. The environmental dynamics demands the reuse of industrial wastes, but such use may lead to situations of environmental pollution when the wastes are poorly handled or applied in excessive amounts. In addition, there are a few studies that evaluate the composition of vinasses derived from the production of cachaça and its suitability to the fertigation. In this context, the present work aimed to evaluate the influence of the sugarcane management and variety on the composition of the vinasse from alembic cachaça. A randomized block design was utilized in a factorial 3X3, with three varieties (RB867515, RB966928 and RB855453) and three cane managements (conventional, organic and control). The experiment had four repetitions for each management and variety, with 9 treatments and 36 parcels in the totality. The samples of vinasse were evaluated for pH and concentrations of macronutrients and micronutrients (Carbon, Nitrogen, Carbon/Nitrogen, Phosphorus, Potassium, Calcium, Magnesium, Sulfur, Iron, Copper, Manganese and Zinc). The results were submitted to analysis of variance (ANOVA) and when differences were significant, Tukey´s test was applied by using Assistat program. There was significant effect of the management (organic and conventional) only on three elements of the vinasse composition, C, K and Mg, the highest concentrations were observed in the vinasse coming from conventional cane management. Regarding cane variety, there was significant effect only on Ca and Mg in the variety RB867515 and RB855453, respectively. The conclusion is that the sugarcane management and the variety had a little influence on the vinasse composition from alembic cachaça. The vinasse composition varied more in accordance with the conditions of distillation of the fermented must for the production of cachaça. The vinasses obtained in the present work, regardless the cane management and variety, presented composition rich in macronutrients and micronutrients when compared to the cachaça or ethanol vinasse compositions reported in literature, featuring N, P, K, Ca, Mg, S, Fe and Cu.
Sugarcane managements and varieties on the composition of the alembic cachaça vinasse
Keywords: Cachaça; Vinhaça; Macro e Micronutrientes; Vinasse; Macronutrients; Micronutrients; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS; CIENCIAS BIOLOGICAS::GENETICA::GENETICA VEGETAL